Drill-assisted, fluoroscopy-guided vertebral body access for radiofrequency ablation: Technical case series. Issue 5 (October 2015) - Wallace, Adam N; Chang, Randy O; Tomasian, Anderanik; Jennings, Jack W
Radiofrequency ablation is a valuable therapy for palliation of painful spinal metastases and local tumor control; however, accessing the vertebral body can be difficult and time consuming with traditional manual needles. Herein, we report our initial experience using a drill-assisted, fluoroscopy-guided technique for accessing the vertebral body for radiofrequency ablation.